IMR 665: Management of Audio Visual Records & Archives. Individual assignment: Article summary / Yasmin Shukri - Shukri, Yasmin (2015)
Article on: Article 1 - “Thematic description of audio-visual information on television” Article 2 - “The production and distribution of audiovisual works via new media in the light of European media policy: constraints and opportunities”